Peningkatan Kualitas SDM Kelurahan Batu Ampar Melalui Workshop Kendaraan Roda Dua - Kholiq Deliasgarin Radyantho; Herman Susilo; Jamal Nur Faisal; Jeriko Silalahi; Ridhwan Haliq; Devy Setioroni Sa'adiyah; Muchammad Jamil; Andre Amba Matarru; Dini Arianti (CV. Multi Kreasi Media, 2023)
Improving community expertise through motorbike maintenance training is carried out as a form of community service. This was done to help improve the quality of human resources (HR) in the community of Batu Ampar Region, North Balikpapan. The final target of each activity provided basic ability to compete in terms of skills and the opportunity to open new job opportunities. Human resources are the subject or object of development, covering the entire human life cycle, from conception to the end of life. Therefore, developing the quality of human resources is very important, especially in small things. Based on the cycle above, there needs to be an effort to provide alternative solutions that can improve quality, one of which is regarding vehicle maintenance knowledge. Community service activities carried out by ITK Mechanical Engineering and SAA (Student Automotive Association). The general activities carried out are divided into 3, such as basic automotive workshops, basic automotive practices, and free service. After being provided with material about motorbike maintenance, the community is equipped with motorbike maintenance practices with the hope that the community can independently open a repair shop (independent repair shop).